Child Protection between Islamic Jurisprudence and Emirati Legislation: Comparative Study - Basahib, Amal Salem (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The study aims to identify the principles of child protection in Islam, compare them with the UAE legislation, and clarify points of agreement and differences between them. Methods: The study adopted the descriptive, inductive, analytical, and comparative approach, which is based on studying, analyzing, and extrapolating legal texts and the corresponding legal texts in the UAE legislation, Federal Law No. (3) of 2016 on Child Rights Law, formerly known as (Wadeema Law). Results: Emirati legislation differed from Islamic jurisprudence in defining ‘the child’ to which protection should be secured, in terms of determining the beginning and end of childhood. On this basis, Islamic jurisprudence distinguishes between a boy and a minor in that the child may reach the age of majority before puberty, and he may reach the age of puberty and not be characterized as being mature. The UAE legislation defines the beginning of childhood from the time of birth until the age of eighteen. The UAE legislation has approved the general principles of child protection in Islamic jurisprudence and approved the mechanisms for achieving such protection. Conclusions: The research recommended amending the legal text related to the definition of the child in the UAE law in line with what was decided by Islamic jurisprudence to determine the beginning and end of the childhood stage since there is a difference between them. Regarding protection mechanisms, there is a great similarity between Islamic jurisprudence and the UAE Child Rights Law.